Fenomena Mahar Politik dalam Pemilihan Umum di Indonesia Perspektif Hukum Islam - Qoni' Afifah; Hendrik Kurniawan; Muhammad Abdu Maulana (Jurnal Hukum Lex Generalis, 2025)
The provision of political dowries in Indonesia has been rampant for a long time, every time an election approaches, issues arise regarding cases of giving political dowries. For example, in the run-up to the simultaneous elections in 2024, every candidate who wants to run as a legislative member prepares a fantastic amount of dowry funds to win a seat in parliament. The existence of this political dowry has an impact on the weakness of democracy in Indonesia and is contrary to Islamic law. So that researchers are interested in discussing this issue from two points of view, First, What is the view of positive law and the impact of political dowries on democracy in Indonesia?; Second, What is the view of Islamic law on the practice of political dowries in Indonesia? The research method used is normative legal research using a statutory approach.